SOCIAL PROTECTION SYSTEM OF THE POPULATION IN THE CONTEXT OF SOCIAL MANAGEMENT - A. F. Borisov; E. V. Domashova (Вестник университета)
A definition of social management has been given, a narrow and broad understanding of social management have been highlighted. The structural elements of social protection defined by the system approach have been clearly delineated and defined. The importance and relevance of public administration of the social protection system of the population, which covers more and more of the population, has been noted and it becomes more targeted. The system of social protection within the framework of social management has been considered. It has been noticed that in recent years, social problems escalated in Russia, characterized by a decrease in the level and quality of life of the broad segments of the population. The current social situation requires implementation of a set of measures aimed at improving social relations in society, enhancing the social well-being of people.